2020
DOI: 10.1111/desc.12984
|View full text |Cite
|
Sign up to set email alerts
|

EEG phase synchronization during semantic unification relates to individual differences in children’s vocabulary skill

Abstract: As we listen to speech, our ability to understand what was said requires us to retrieve and bind together individual word meanings into a coherent discourse representation. This so-called semantic unification is a fundamental cognitive skill, and its development relies on the integration of neural activity throughout widely distributed functional brain networks. In this proof-of-concept study, we examine, for the first time, how these functional brain networks develop in children. Twenty-six children (ages 4-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…Similar developmental differences in the distribution and duration of the N400 in response to semantic violations have been reported and related to children's age and/or vocabulary skill (e.g., Khalifian, 2016 ; Schneider and Maguire, 2018 ; Panda et al, 2021 ). While informative, the N400 is calculated at the single word level in many of these studies, limiting our understanding of how differences at the word level manifest over the course of the entire sentence.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similar developmental differences in the distribution and duration of the N400 in response to semantic violations have been reported and related to children's age and/or vocabulary skill (e.g., Khalifian, 2016 ; Schneider and Maguire, 2018 ; Panda et al, 2021 ). While informative, the N400 is calculated at the single word level in many of these studies, limiting our understanding of how differences at the word level manifest over the course of the entire sentence.…”
Section: Discussionsupporting
confidence: 68%
“…While informative, the N400 is calculated at the single word level in many of these studies, limiting our understanding of how differences at the word level manifest over the course of the entire sentence. Of the few studies which have examined developmental differences in theta engagement over the course of a sentence, many focus on processing demands surrounding semantic anomalies ( Schneider and Maguire, 2018 ; Panda et al, 2021 ), and fail to examine whether differences in theta band engagement exist based on retrieval versus unification processes ( Schneider et al, 2016 ). Building on these past studies, we were able to pinpoint two unique ways in which theta activation occurred, and how the localization and timing of these two responses varied, as a function of age.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that attentional modulation induced by consistent visual cues may facilitate learning. This idea fits well with recent results obtained during an audio-visual movie visualization task and showing increased frontal-occipital phase synchrony in the sensor space when children listened to well-formed sentences compared to semantically incongruous sentences ( Panda et al, 2020 ). Previous studies using similar methodologies have also shown that the neural tracking of a specific talker in higher-order auditory regions differs between attended and non-attended speech input ( Ding and Simon, 2012 ; Lakatos et al, 2013 ).…”
Section: Discussionsupporting
confidence: 91%
“…Further research shows that neural synchronization to the stimulus only occurs for attended stimuli ( Ding and Simon, 2012 ; Lakatos et al, 2013 ), whereas when the tracking of the stimulus is not possible, speech perception and comprehension is impoverished ( Ahissar et al, 2001 ; Luo and Poeppel, 2007 ). These findings suggest that top-down attentional mechanisms modulate speech processing in children ( Wang et al, 2014 ; Panda et al, 2020 ; Ríos‐López et al, 2020 ). One way to investigate oscillatory brain activity is to use frequency-tagging analysis, which shows the fine neural synchronization in response to both auditory and visual stimuli ( Doesburg et al, 2012 ; Kim et al, 2007 ; Keitel et al, 2014 ; Covic et al, 2017 ; Nozaradan et al, 2012 ).…”
Section: Introductionmentioning
confidence: 78%
“…Gratton and Coles (1983) method was used to correct for eye movements (50), and trials with an amplitude difference of 200μV over a 200ms interval, or with an amplitude >±200μV were rejected, resulting in 42.18 (SD = 5.89) Go trials and 44.35 (SD = 5.41) No-Go trials entering analysis. Connectivity between EEG sensors was calculated as in Panda et al (51). Specifically, trial-by-trial data (from 3s pre-stimulus to 3s post-stimulus) from each participant were z-scored and filtered into canonical frequency-bands: (1-3Hz; 4-7Hz; 8-13Hz; 14-29Hz; 30-90Hz).…”
Section: Eeg Preprocessing and Phase Synchronymentioning
confidence: 99%